The Challenge of Values Education in the Generation Alpha Era: Initiating a New Direction for Elementary Civics Education in Response to the Digital Moral Crisis - Salasa Shofyani; Yacobus Ndona; Surya Dharma (Civiliza Publishing, Indonesia., 2026)
Generation Alpha grew up in a digital environment that made it a major social space, but their technical prowess was not in line with moral maturity. The phenomenon of language ethics degradation, cyberbullying, and low digital empathy in elementary schools indicate an escalation of moral crisis that requires serious handling. This research aims to analyze the challenges of value education in the Alpha Generation and formulate a new direction of learning in Pancasila and Citizenship Education (PKn) through the integration of digital citizenship. A qualitative approach with the library research method is used to review the scientific literature and factual data related to the digital moral crisis. The results of the study formulated two main strategies: (1) repositioning PKn material by converting Pancasila values into cyber ethics; and (2) transformation of learning methodology using a digital moral dilemma-based Case Method. This study concludes that the new direction of PKn requires adaptive curriculum transformation and strong synergy in the Tricenter Education ecosystem so that students' ethical character habituation is formed in its entirety in the real and virtual worlds.